TUTURAN PERINTAH DALAM WACANA PERKULIAHAN DI PROGRAM MAGISTER PENDIDIKAN BAHASA INDONESIA PASCASARJANA UNIVERSITAS TADULAKO - Kasim, Fatma (BAHASANTODEA, 2015)
Abstract This research aimed at describing the use of directive act that comprised the form of directive command, (2) the function of directive command, (3) the strategy of directive command on the Lecturing Discourse at Master Program Indonesian Language of Graduate Program of Tadulako University. This research employed qualitative descriptive method. Data were gathered through two techniques: (1) recording, and (2) observation. The Subject of this research was lectures and student of Master Program of Indonesian Language of Postgraduate Program of Tadulako University, the 2012-2014 academic year. The technique of data analysis was interactive model. The analysis comprised four stages: (1) data collection, (2) data reduction, (3) data presentation, and (4) verification/conclusion. The results show that on the Lecturing Discourse at Master Program of Indonesian Language of Postgraduate Program of Tadulako University, the act of directive command was stated in the form of command directive command, and it was an obligation. On the function of command, it was to limit the question and to ask explanation. Strategies applied on the act of directive command were direct and indirect ones. Direct strategy applied on the act of directive command and direct command with argument. Indirect strategy comprised indirect command act were adopted by lectures for the certain thing, and limiting kinds of question and statement. Form, function, and strategy of directive command act were adopted by lecturers for the certain aims, such as asking explanation to certain thing, and limiting kinds of questions stated by students in the process of instruction. One the students speech, the command was used to express common command with the function to command and ask explanation to other students. The choice of the strategy was related to the function of speech shared. Relating to this command, direct and indirect strategy can be used to express certain intention. Keywords: Speech act, directive act, command act, the lecturing discourse